Assessing the Reliability and Validity of the Persian Version of the Chronic Pelvic Pain Questionnaire in Women - Mirzaei, Mahboubeh; Daneshpajooh, Azar; Bagherinasabsarab, Mohammadali; Bahreini, Fatemeh; Yazdanpanah, Fatemeh (Urology Journal, 2020)
Purpose: There is a need for developing a standard and approved tool to assess chronic pelvic pain (CPP) in Iranian women. The aim of this study was to investigate the reliability and validity of the Persian version of the pelvic pain and urinary/frequency (PUF) questionnaire in Iranian women with CPP. Materials and Methods: This cross-sectional study was performed on 50 females with CPP referred to the urology clinic of Kerman University of Medical Sciences from 2018 to 2019. Initially, the PUF questionnaire was translated into Persian and then back translated into English. The face validity of the tool was evaluated by being tested on 50 patients who had different literacy levels to ensure its understandability and acceptability by patients. The construct validity was evaluated through both exploratory and confirmatory factor analyses. The internal consistency was also analyzed by determining Cronbach's alpha coefficient and test-retest method. Results: The Persian version of the questionnaire was compatible with the original English version. The Kisser sampling adequacy index was calculated on the data before extracting the factors indicating good factor accessibility of the questionnaire statements. The construct validity of the questionnaire was confirmed using exploratory and confirmatory factor analyses. The internal consistency parameters were also acceptable. Cronbach's alpha coefficient of the whole questionnaire, as well as the coefficients of the "signs/symptoms" and "unpleasant feelings" domains were 77%, 74%, and 78%, respectively. Conclusion: The developed Persian version of the PUF questionnaire retrieved a good validity and reliability.